Promoted inhibition of TLR4/miR-155/ NFkB p65 signaling by cannabinoid receptor 2 agonist (AM1241), aborts inflammation and progress of hepatic fibrosis induced by thioacetamide. (25th February 2021) - Ali, Alaa M.; El-Tawil, Osama S.; Al-Mokaddem, Asmaa K.; Abd El-Rahman, Sahar S.
Abstract: The endocannabinoid system plays a pivotal role, whether it is promoting or dampening hepatic fibrosis. This study investigated the role of Cannabinoid receptor 2 ( CB2 ) activation by the synthetic analog (AM1241) on revoking the progress of liver fibrosis. Thioacetamide (TAA) was used to induce liver fibrosis in rats for three weeks followed by its concurrent administration with AM1241 at two different doses for another three weeks. Markers for liver function and oxidative stress, hepatic TNF-α, IL-1β and IL-6, qRT-PCR expression of Toll like receptor 4 (TLR4), TGF-β1, α-SMA and microRNA-155 (miR-155) genes, Western blot for protein levels of Vimentin and E-cadherin, immunohistochemical expression of NFκB p65 and histopathology of liver tissue were all investigated. AM1241 administration significantly maintained liver function markers and decreased; malondialdehyde, Vimentin, TLR4, TGF-β1, α-SMA and miR-155 genes expression, NFκB p65 immune-expression and pro-inflammatory cytokines (TNF-α, IL-1β and IL-6). Additionally, AM1241 significantly increased E-Cadherin level, GSH and SOD content. Histologically, AM1241 limited fibroplasia extension, and broke the itinerary of bridging fibrosis. In conclusion, activation of the CB2 receptors by AM1241 promoted liver regeneration and overrun the progression of liver fibrosis through; inhibition of TLR4/miR-155/NFκB p65 pathway, suppression of pro-inflammatory IL-6, IL-1β and TNF-α, reducing TGF-β1, α-SMA, Vimentin and up-regulating E-Cadherin. Graphical abstract: Image 1 Highlights: AM1241; a Cannabinoid receptor 2 agonist aborts the ongoing hepatic fibrosis. AM1241 impedes NFkB p65 expression via deactivating TLR4/miR-155 pathway. AM1241 suppresses the inflammation and fibrosis via inhibiting NFkB p65. AM1241 down regulates TNF-α, IL-6, Vimentin and upgrade E-Cadherin level. AM1241 restores hepatic cells by maintaining antioxidant system.